Femoral nerve block versus intravenous fentanyl in adult patients with hip fractures - a systematic review - Hartmann,Flávia Vieira Guimarães (2017)
Abstract Background: Hip fractures configure an important public health issue and are associated with high mortality taxes and lose of functionality. Hip fractures refer to a fracture occurring between the edge of the femoral head and 5 cm below the lesser trochanter. They are common in orthopedic emergencies. The number of proximal femoral fractures is likely to increase as the population ages. The average cost of care during the initial hospitalization for hip fracture can be estimated about US$ 7,000 per patient. Femoral fractures are painful and need immediate adequate analgesia. Treating pain femoral fractures is difficult because there are limited numbers of analgesics available, many of which have side effects that can limit their use. Opiates are the most used drugs, but they can bring some complications. In this context, femoral nerve blocks can be a safe alternative. It is a specific regional anesthetic technique used by doctors in emergency medicine to provide anesthesia and analgesia of the affected leg. Objective: To compare the analgesic efficacy of intravenous fentanyl versus femoral nerve block before positioning to perform spinal anesthesia in patients with femoral fractures assessed by Pain Scales. Methods: A systematic review of scientific literature was conducted. Studies described as randomized controlled trials comparing femoral nerve block and traditional fentanyl are included. Two reviewers (MR and FH) independently assessed potentially eligible trials for inclusion. The methodology assessment was based on the tool developed by the Cochrane Collaboration for assessment of bias for randomized controlled trials. The Cochrane Library, Pubmed, Medline and Lilacs were searched for all articles published, without restriction of language or time. Results: Two studies were included in this review. Nerve blockade seemed to be more effective than intravenous fentanyl for preventing pain in patients suffering from a femoral fracture. It also reduced the use of additional analgesia and made lower the risk for systemic complications. Femoral nerve block reduced the time to perform spinal anesthesia to the patient who will be subjected to surgery and facilitate the sitting position for this. Conclusion: The use of femoral nerve block can reduce the level of pain and the need for additional analgesia. There are less adverse systemic events associated with this and the procedure itself does not offer greater risks. More studies are required for further conclusions.